Morrenain b I, a Papain-like Endopeptidase from the Latex of Morrenia brachystephana Griseb. (Asclepiadaceae) - Vairo Cavalli, Sandra Elizabeth (2003)
A new cysteine endopeptidase (morrenain b I) has been purified and characterized from the latex of stems and petiols of Morrenia brachystephana Griseb. (Asclepiadaceae). Morrenain b I was the minor proteolytic component in the latex but showed higher specific activity than morrenain b II, which was the main active fraction. Both enzymes showed similar pH profiles and molecular masses, but kinetic parameters and N-terminal sequences were quite distinct, demonstrating that they are different enzymes instead of different forms of the same enzyme.